2003
DOI: 10.3998/ark.5550190.0004.a22
|View full text |Cite
|
Sign up to set email alerts
|

The first example of a highly non-symmetric ozonolysis of a sugar derived norbornene system

Abstract: The completely regioselective fragmentation of the primary ozonide formed during the ozonolysis of an unsymmetrical substituted norbornene system in the presence of methanol appears to be controlled by remote substituents and affords a tetrasubstituted cyclopentane moiety as a unique product in an almost quantitative yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Further studies by this group have addressed the issue of the fragmentation of the primary ozonide in carbohydrate-derived norbornene systems. They showed that, in participating solvents, the remote substitution is responsible for the regioselective fragmentation of the intermediate ozonide [129,130,131].…”
Section: Reactions Of Hex-2-enopyranosidesmentioning
confidence: 99%
“…Further studies by this group have addressed the issue of the fragmentation of the primary ozonide in carbohydrate-derived norbornene systems. They showed that, in participating solvents, the remote substitution is responsible for the regioselective fragmentation of the intermediate ozonide [129,130,131].…”
Section: Reactions Of Hex-2-enopyranosidesmentioning
confidence: 99%